2021
DOI: 10.3389/fendo.2021.689887
|View full text |Cite
|
Sign up to set email alerts
|

Tolvaptan in the Management of Acute Euvolemic Hyponatremia After Transsphenoidal Surgery: A Retrospective Single-Center Analysis

Abstract: IntroductionSyndrome of inappropriate antidiuresis (SIAD) can be a complication of hypothalamus-pituitary surgery. The use of tolvaptan in this setting is not well established, hence the primary aim of this study was to assess the sodium correction rates attained with tolvaptan compared with standard treatments (fluid restriction and/or hypertonic saline). Furthermore, we compared the length of hospital stay in the two treatment groups and investigated the occurrence of overcorrection and side effects includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…With a 100% sensitivity and 66.7% specificity, NT-proBNP can accurately predict hypovolemia and a cut-off value of 125 pg/ml differentiates CSW from SIADH (with 87.50% sensitivity and 93.33% specificity) [81]. The incidence of SIADH following transsphenoidal surgeries ranges from 1.8% to 37%, and tolvaptan has been reported to yield significant sodium correction rates, notwithstanding adverse effects, therefore reducing the length of hospital stay [83][84][85][86][87][88]. Hyponatremia due to SIADH is also associated with schwannoma, owing to adrenal insufficiency and panhypopituitarism caused by an intra-or suprasellar mass [89].…”
Section: Postoperative Hyponatremiamentioning
confidence: 99%
“…With a 100% sensitivity and 66.7% specificity, NT-proBNP can accurately predict hypovolemia and a cut-off value of 125 pg/ml differentiates CSW from SIADH (with 87.50% sensitivity and 93.33% specificity) [81]. The incidence of SIADH following transsphenoidal surgeries ranges from 1.8% to 37%, and tolvaptan has been reported to yield significant sodium correction rates, notwithstanding adverse effects, therefore reducing the length of hospital stay [83][84][85][86][87][88]. Hyponatremia due to SIADH is also associated with schwannoma, owing to adrenal insufficiency and panhypopituitarism caused by an intra-or suprasellar mass [89].…”
Section: Postoperative Hyponatremiamentioning
confidence: 99%
“…Baseline plasma sodium ≤121 mmol/L and blood urea nitrogen ≤10 mg/dL (plasma urea of ≤3.7 mmol/L) are associated with a significantly greater rise in plasma sodium following tolvaptan ( 89 ). The use of tolvaptan for SIAD in the postoperative pituitary surgery setting is mostly limited to retrospective studies and case reports or series ( 90–93 ). In postoperative pituitary patients, a single-dose of tolvaptan is effective in normalizing plasma sodium and reducing the duration of hospital admission ( 90 ); however, it is associated with a risk of overcorrection.…”
Section: Managementmentioning
confidence: 99%
“…The use of tolvaptan for SIAD in the postoperative pituitary surgery setting is mostly limited to retrospective studies and case reports or series ( 90–93 ). In postoperative pituitary patients, a single-dose of tolvaptan is effective in normalizing plasma sodium and reducing the duration of hospital admission ( 90 ); however, it is associated with a risk of overcorrection. In a retrospective study, Indirli et al found higher correction rates of plasma sodium with tolvaptan (median dose 15 mg) than standard treatment which included fluid restriction and/or hypertonic saline (12 mmol/L/24 hour vs 1.8 mmol/L/24 hours).…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations